Susceptibility Loci for Preeclampsia on Chromosomes 2p25 and 9p13 in Finnish Families - Laivuori, Hannele (The American Society of Human Genetics, 2003)
Preeclampsia is a common, pregnancy-specific disorder characterized by reduced placental perfusion, endothelial dysfunction, elevated blood pressure, and proteinuria. The pathogenesis of this heterogeneous disorder is incompletely understood, but it has a familial component, which suggests that one or more common alleles may act as susceptibility genes. We hypothesized that, in a founder population, the genetic background of preeclampsia might also show reduced heterogeneity, and we have performed a genomewide scan in 15 multiplex families recruited predominantly in the Kainuu province in central eastern Finland. We found two loci that exceeded the threshold for significant linkage: chromosome 2p25, near marker D2S168 (nonparametric linkage [NPL] score 3.77; P=.000761) at 21.70 cM, and 9p13, near marker D9S169 (NPL score 3.74; P=.000821) at 38.90 cM. In addition, there was a locus showing suggestive linkage at chromosome 4q32 between D4S413 and D4S3046 (NPL score 3.13; P=.003238) at 163.00 cM. In the present study the susceptibility locus on chromosome 2p25 is clearly different (21.70 cM) from the locus at 2p12 found in an Icelandic study (94.05 cM) and the locus at 2q23 (144.7 cM) found in an Australian/New Zealand study. The locus at 9p13 has been shown to be a candidate region for type 2 diabetes in two recently published genomewide scans from Finland and China. The regions on chromosomes 2p25 and 9p13 may harbor susceptibility genes for preeclampsia.